Involving people with dementia and their carers in dementia education for undergraduate healthcare professionals: a qualitative study of motivation to participate and experience. (June 2019) - Cashin, Zoe; Daley, Stephanie; Hebditch, Molly; Hughes, Leila; Banerjee, Sube
ABSTRACT: Background: There is a need to improve dementia education to prepare future generations of healthcare professionals to deal with the increasing challenges they will face. Time for Dementia is an innovative undergraduate education program for medical, nursing, and paramedic students in the south of England. Success of the program is dependent upon the participation of families (people with dementia and their carers). This qualitative study seeks to explore the motivation and experiences of the families taking part in the program. Methods: A topic guide was developed to understand factors influencing motivation and retention. A purposeful sample of participant families, who had at least 12 months of involvement in the program, were selected from a cohort of 282 families and were invited to take part in an in-depth qualitative interview. Interviews were audio recorded, transcribed verbatim, and analyzed using thematic analysis. This was subsequently refined in an on-going process of analysis aided by the use of Nvivo 11. Interviewing stopped when thematic saturation was reached. Results: Eighteen families took part in an in-depth qualitative interviews. Four themes were identified from the analysis. These themes were motivators, value to family, value to the person with dementia, and student factors. Conclusions: This study identifies underpinning factors that motivate families to join dementia education programs and the impact of such programs upon them. We found that engagement in such programs can have therapeutic benefits to participants, and do not cause harm. These findings can be used to strengthen recruitment and enhance family involvement in similar programs.